ANALISIS EFEKTIFITAS PENGGUNAAN ANGGARAN PELATIHAN INSERSI IUD DAN IMPLANT BAGI DOKTER TERHADAP PENINGKATAN AKSEPTOR KB BARU PADA KANTOR PERWAKILAN BKKBN PROVINSI KEPULAUAN BANGKA BELITUNG TAHUN 2013-2017 - T. Aji Manggala, Nazamuddin; Ruben Manullang, Rizal; Prima Nugroho, Stefanus (Jurnal Progresif Manajemen Bisnis, 2018)
The large population of Human Resources (HR) is a development force. A large population, accompanied by high quality, is an asset to economic growth. Conversely, a large population if not supported with adequate quality would be a burden on economic development. The data shows that the quality of Indonesia's population the country with the fourth largest population in the world is still very low for example in education, productivity, creativity, work ethic, health degree, and so forth. With this low quality of human resources, the potential of natural wealth owned becomes less meaningful because the Indonesian nation is less able to utilize the wealth. One of the efforts undertaken to reduce the rate of population growth is the National Family Planning Program (PKBN) conducted by the National Family Planning Board (BKKBN). Efforts to reduce birth rates conducted in the National Family Planning Program were conducted by means of contraceptive use by couples of childbearing age to control pregnancy and reduce the birth rate. In relation thereto, the National Family Planning Program gives priority to the use of contraceptive types that have high effectiveness, high protection, and long-term effect on the possibility of pregnancy. One effective method of contraception is the IUD and Implant. In this case, the installation of IUD and implants in KB acceptor should be done by trained medical personnel as well as doctors and midwives who have attended IUD insertion training and implant whose activities are organized by BKKBN. A prerequisite for the implementation of such training is the availability of adequate budgetary support so that all planned program vision and mission can be aligned with the effective use of the required budget. One of the efforts to improve the quality and quality of the doctors is done through training of IUD insertion and implant which must be supported by an adequate budget so that the doctors can explain to the public the benefits of IUD and implant and can perform IUD and implant services properly and safely.